ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA PADA POKOK BAHASAN BANGUN RUANG SISI DATAR DI SMP NEGERI 12 BANDUNG - Eka Khairani Hasibuan (State Islamic University of North Sumatra, 2018)
This research focuses on the effort to describe the difficulties experienced by students in the learning process on the subject of building a flat side room in mathematics learning. This research was conducted in connection with the difficulty of students in learning mathematics on the matter of building a flat side room. Therefore, it takes an effort to to find out the causes of difficulties experienced by students in the process of learning mathematics. One way that can be done is to identify the causes of student learning difficulties experienced by mathematics students during the process of learning mathematics took place in the classroom. This research will be conducted on the students of class VIII SMP Negeri 12 Bandung